The senses of being an enterostomal therapist nurse: complexities involved in the specialty (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To describe the meanings of being an enterostomal therapist considering the complexity of the process of caring for people with wounds, stomas and incontinence. Method: A qualitative, descriptive-exploratory study, conducted through a semistructured interview, between the months of January to April 2018, with 22 graduates from a specialization course in Nursing in Enterostomal Therapy from a public university in the Southeast region, following the snowball technique. Documental research was also carried out in order to complement the data analysis. Results: The interviewed graduates reported that being an enterostomal therapist is taking care of people who have a wound, stoma and/or incontinence, which means they recognized the essence of the specialty. They emphasized that being an enterostomal therapist is to care for people who may be marginalized/stigmatized by society, to work with a focus on the patient’s rehabilitation, seeking social reintegration and independence, and to know how to be an entrepreneur. Conclusion: The meaning of being an enterostomal therapist involves being inserted in a specialty that provides flexibility in the job market and an entrepreneurial character, which gives professional recognition and even financial satisfaction. It is suggested, therefore, that further studies be carried out in this area, contributing to the fields of assistance, teaching, research and extension.